(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article the system of education and place of religion in schools and madrasas of the Kazakh steppe is analyzed. The works of great Kazakh steppe thinkers Abay Konanbayev, Chokan Ualihanov and Ybyrai Altynsarin are examined. Their personality is that of great teachers who contributed to the formation of culture and spiritual life of our people. Among the priceless heritage they left behind are their views on Islam, their views on religion are a real asset and a source for today’s youth. During this period, the future of the Kazakh people, or rather the question of the direction of which will need to adhere to, very worried elite and enlightened people. Whether it was necessary to turn the face to the Muslim East or whether it was necessary to follow the Western direction and be together with the “Russian world”, it was very important to think over this issue in a comprehensive way for the fruitful development of the future of the country. In this regard, a lot of activities and censuses were carried out. The article provides several letters as an example. Kazakh educators, in their turn, wanted to focus not only on religious education but also to give an opportunity to the formation of a certain system of education in general with the help of religious education, according to Kazakh mentality. Key words: enlighteners, Islam, religion, Muslim.